2016
DOI: 10.1007/s13277-016-5259-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imbalances and microRNA transcriptional profiles in patients with mycosis fungoides

Abstract: Mycosis fungoides is the most common type of primary cutaneous T cell lymphoma. We have evaluated CDKN2A losses and MYC gains/amplifications by FISH analysis, as well as expression of miR-155 and members of the oncogenic cluster miR-17-92 (miR17, miR18a, miR19b, and miR92a) in MF patients with advanced disease. Formalin-fixed paraffin-embedded skin biopsies from 36 patients at diagnosis, 16 with tumoral MF (T-MF), 13 in histological transformation to a large T cell lymphoma (TR-MF), and 7 cases with folliculot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
2
15
0
1
Order By: Relevance
“…We found that miR‐155 expression was increased in 57 of the 77 MF samples studied, consistent with one published report (Maj et al , ). We found increasing miR‐155 expression in biopsy samples with increasing severity of lesion type (patch to plaque to tumour) (Figs B and A), consistent with reports demonstrating increased expression of miR‐155 in tumour‐stage MF (van Kester et al , ; Moyal et al , ; Sandoval et al , ; Garaicoa et al , ). The differential expression of the pharmacodynamic biomarker genes was sufficient to cluster biopsies according to lesion type (patch, plaque, or tumour) (Fig A).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that miR‐155 expression was increased in 57 of the 77 MF samples studied, consistent with one published report (Maj et al , ). We found increasing miR‐155 expression in biopsy samples with increasing severity of lesion type (patch to plaque to tumour) (Figs B and A), consistent with reports demonstrating increased expression of miR‐155 in tumour‐stage MF (van Kester et al , ; Moyal et al , ; Sandoval et al , ; Garaicoa et al , ). The differential expression of the pharmacodynamic biomarker genes was sufficient to cluster biopsies according to lesion type (patch, plaque, or tumour) (Fig A).…”
Section: Discussionsupporting
confidence: 89%
“…Mycosis fungoides (MF), the most prevalent subtype of CTCL, can remain indolent or progress from limited patches and plaques in the epidermis to tumour formation in some patients (Willemze et al , ). Many groups have reported overexpression of miR‐155 in skin biopsies from patients with advanced MF compared with controls (van Kester et al , ; Ralfkiaer et al , , ; Moyal et al , ; Marosvari et al , ; Sandoval et al , ; Garaicoa et al , ), which suggests that miR‐155 might play a role in disease progression of MF (Kopp et al , ; Moyal et al , , ). In fact, the measurement of miR‐155 together with two other microRNAs (miR‐203 and miR‐205) has been proposed as a diagnostic tool for MF (Ralfkiaer et al , ; Marstrand et al , ).…”
mentioning
confidence: 99%
“…High CD30 expression is associated with significantly better disease‐specific and disease‐free survival . A recent study demonstrated that genomic alterations, including CDKN2A loss or deletion and C‐MYC gain or amplification, are significantly greater in LCT than in advanced‐stage MF, and both these alterations are found in 54% of LCT . Our patient had LCT with atypical T‐cells expressing predominantly CD8 but negative for CD30.…”
Section: Discussionmentioning
confidence: 54%
“…Many miRs are implicated in the pathogenesis of cancers and can serve as biomarkers, given high correlation between their levels and disease diagnosis, progression, and responsiveness to therapy. Several studies have reported that miR expression profiles are different in CTCL and BID, including miR-155, miR-203, miR-205, miR-92a, miR-93, miR-15a, miR-16, let-17a, let-17d, and let-7f (Benner et al, 2012a;Garaicoa et al, 2016;Narducci et al, 2011;Papadavid et al, 2016;Taylor et al, 2003;van Kester et al, 2011). There is very limited study on global analysis of noncoding RNA in CTCL diagnosis.…”
Section: Introductionmentioning
confidence: 99%